Extraosseous aneurysmal bone cyst in dogs: a report of two cases - Cubillo Rodríguez, Viviana (2019)
During a routine check-up in a 6-year-old intact male Labrador Retriever and a 6-year-old intact male Boxer, a mass in their pelvic cavities was found. Both dogs were clinically healthy and did not display any clinical symptoms. The masses were surgically removed and sent to a pathology laboratory for analysis. The histopathological evaluation of both lesions diagnosis was: extraosseous aneurysmal bone cysts. This report describes the macroscopic and histopathological characteristics of the cysts in both patients.